Optimizing the shape of mechanical elements and structures - Seireg, Ali (Mechanical engineering (Marcel Dekker, Inc.), 1997)
This hands-on reference introduces a wide variety of practical approaches to the synthesis and optimization of shapes for mechanical elements and structures emphasizing the simplest methods possible for achieving the best results without mathematical complexity, especially computer solutions.